2021
DOI: 10.3390/biomedicines9030312
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomes in Breast Cancer Diagnosis

Abstract: The importance of molecular re-characterization of metastatic disease with the purpose of monitoring tumor evolution has been acknowledged in numerous clinical guidelines for the management of advanced malignancies. In this context, an attractive alternative to overcome the limitations of repeated tissue sampling is represented by the analysis of peripheral blood samples as a ‘liquid biopsy’. In recent years, liquid biopsies have been studied for the early diagnosis of cancer, the monitoring of tumor burden, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 113 publications
0
28
0
Order By: Relevance
“…Additionally, it also provides us an opportunity to explore biomarkers for better diagnosis and prognosis at an early stage [ 166 , 167 ]. In 2016, two test kits on fluid biopsy-based approaches were available to detect prostate and lung diseases (ExoDx ® prostate and ExoDx ® Lung, Exosome Diagnostics Inc., Waltham, MA, U.S.A) [ 87 , 168 , 169 ]. Breast cancer-derived exosomes have also been considered as a potential indicator of cancer progression [ 114 ].…”
Section: Clinical Application Of Exosomesmentioning
confidence: 99%
“…Additionally, it also provides us an opportunity to explore biomarkers for better diagnosis and prognosis at an early stage [ 166 , 167 ]. In 2016, two test kits on fluid biopsy-based approaches were available to detect prostate and lung diseases (ExoDx ® prostate and ExoDx ® Lung, Exosome Diagnostics Inc., Waltham, MA, U.S.A) [ 87 , 168 , 169 ]. Breast cancer-derived exosomes have also been considered as a potential indicator of cancer progression [ 114 ].…”
Section: Clinical Application Of Exosomesmentioning
confidence: 99%
“…EVs are involved in several biological processes such as antigen presentation, immune regulation, apoptosis evasion, drug resistance, and angiogenesis [ 25 , 26 , 27 , 28 ]. Based on their size, they are classified into apoptotic bodies (50–5000 nm) released by apoptotic cells, shedding microvesicles/ectosomes (100–1000 nm) produced by budding from the plasma membrane, and exosomes (30–150 nm) that originate from intracellular multivesicular bodies and are secreted in the extracellular space upon fusion with the plasma membrane [ 20 , 23 , 29 ]. They carry proteins, metabolites, lipids, mRNA, miRNA, long-non-coding RNA, and DNA [ 24 , 25 , 26 , 30 , 31 ].…”
Section: Extracellular Vesicles and Micrornasmentioning
confidence: 99%
“…In particular, miRNAs secreted by cancer cells are packed into extracellular vesicles (EVs) and released into peripheral blood. EVs are largely involved in the cross-talk between cancer cells and the microenvironment [ 20 , 21 ]. The important involvement of EVs and miRNA in ontogenetic processes and their availability in biological fluids, make these molecules optimal biomarkers in oncology [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a type of extracellular vesicles (EVs), exosomes are homogenous membrane vesicles (ranging from 30 to 150 nm), derived from the multivesicular bodies (MVBs), formed by the budding of the endosomal membranes and released in the extracellular space upon fusion with the plasma membrane (7,8). In 1983, exosomes were discovered and considered to operate as cellular garbage disposal (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, exosomes were discovered and considered to operate as cellular garbage disposal (9,10). With the investigation of biological function, angiogenesis, immunity, and metastasis have been demonstrated to be regulated by exosomes from cancer cells, making a critical effect in facilitating tumorigenesis (8,11,12). Interestingly, some studies indicated that one part of the human epidermal growth factor receptor (HER) family was exosome associated in breast, gastric, and pancreatic cancers (8,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%